Covalent organic frameworks as electrode materials for rechargeable metal‐ion batteries. Issue 2 (9th February 2023) - Wu, Manman; Zhou, Zhen
Abstract: Covalent organic frameworks (COFs), as a class of crystalline porous polymers, featuring designable structures, tunable frameworks, well‐defined channels, and tailorable functionalities, have emerged as promising organic electrode materials for rechargeable metal‐ion batteries in recent years. Tremendous efforts have been devoted to improving the electrochemical performance of COFs. However, although significant achievements have been made, the electrochemical behaviors of developed COFs are far away from the desirable performance for practical batteries owing to intrinsic problems, such as poor electronic conductivity, the trade‐off relationship between capacity and redox potential, and unfavorable micromorphology. In this review, the recent progress in the development of COFs for rechargeable metal‐ion batteries is presented, including Li, Na, K, and Zn ion batteries. Various research strategies for improving the electrochemical performance of COFs are summarized in terms of the molecular‐level design and the material‐level modification. Finally, the major challenges and perspectives of COFs are also discussed in the aspect of large‐scale production and electrochemical performance improvements. Abstract : Covalent organic frameworks (COFs), as a class of crystalline porous polymers, have emerged as promising organic electrode materials for rechargeable metal‐ion batteries in recent years. Here we summarize the latest progress of COFs in Li, Na, K, and Zn ion batteries, and discuss various research strategies, major challenges, and perspectives.